2020
DOI: 10.3390/molecules25204773
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Gold and Silver Nanoparticles by Using Amorphophallus paeoniifolius Tuber Extract and Evaluation of Their Antibacterial Activity

Abstract: In this report, we discussed rapid, facile one-pot green synthesis of gold and silver nanoparticles (AuNPs and AgNPs) by using tuber extract of Amorphophallus paeoniifolius, and evaluated their antibacterial activity. AuNPs and AgNPs were synthesized by mixing their respective precursors (AgNO3 and HAuCl4) with tuber extract of Amorphophallus paeoniifolius as the bio-reducing agent. Characterization of AuNPs and AgNPs were confirmed by applying UV-vis spectroscopy, field-emission scanning electron microscopy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 47 publications
4
17
0
Order By: Relevance
“…The findings of the antibacterial assay revealed that there was a clear increase in the activities of AgNPs against S. aureus . These findings were analogous to the previous reports in the literature that silver nanoparticles had strong antibacterial activities [ 55 , 76 , 77 ]. Composite was also active for S. aureus , while unaccompanied nanoparticles of L. lucidum were more significantly active.…”
Section: Resultssupporting
confidence: 92%
“…The findings of the antibacterial assay revealed that there was a clear increase in the activities of AgNPs against S. aureus . These findings were analogous to the previous reports in the literature that silver nanoparticles had strong antibacterial activities [ 55 , 76 , 77 ]. Composite was also active for S. aureus , while unaccompanied nanoparticles of L. lucidum were more significantly active.…”
Section: Resultssupporting
confidence: 92%
“…Thus far, utilization of leaf and fruit extracts of various plants are the most commonly reported. Among many plants, sweet potato is an interesting candidate for this purpose, not only because it contains high concentration of various reducing agents (e.g., reducing sugars, phenolic compounds, vitamin C, β-carotene), but also because it has a lot of unexplored regional variants, each offering slightly different compositions to one another [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The XRD analysis confirming that the produced SeNPs possessed a hexagonal phase structure (more stable form at room temperature), It's worth noting that the broadening of the XRD peaks indicates that the grain sizes of the produced powder are on the nano scale. The Scherer formula equation applied to calculate the average crystalline size for all assigned peaks of the synthesized SeNPs was obtained equal to 5.08 nm [34]. The contrasting of this result appear in XRD spectrum of the SeNPs prepared by bio-reduction of sodium selenate (Na 2 SeO 4 ) exhibited a broad peak at a 2theta angle of 15-35 degree indicating amorphous nature of selenium crystal this return stabilizer effect [35].…”
Section: X-ray Diffractionmentioning
confidence: 94%